The Growth of Critical Thinking among students of the University of Zakho - Faculty of Humanities, according to the two variables, Study Level (stage) and age - Haji, Zheerwan; Saeed, Deyar (Humanities Journal of University of Zakho, 2021)
Language and thought are linked to each other and different types of thinking can be identified through it. Linguistic thinking is linked to the environment from which the individual takes the language. This study entitled “The Growth of Critical Thinking among students of the University of Zakho - Faculty of Humanities, according to the two variables, Study Level (stage) and age”, which shows the relationship of research variables as a specific stage of study to critical thinking according to SPSS statistics and the descriptive approach. This study, according to the objectives of the research, to shed light on the relationship of the variables with the critical thinking skills of the California test (C-2000) among the first and fourth year students of the Department of Humanities - Morning Studies, University of Zakho for the academic year 2019-2020.